2013
DOI: 10.1515/cclm-2013-0361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the N Latex free light chain assay in the diagnosis and monitoring of AL amyloidosis

Abstract: Background: We compared a novel assay for free light chain (FLC) quantitation based on monoclonal antibodies (N-Latex, Siemens, Germany) to the established polyclonal antibody-based assay (Freelite

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Overall response rates/CR rates in patients with high vs low baseline dFLC (.124.2 vs #124.2 mg/L, cutoff per the median baseline dFLC) after cycles 1, 2, and 4, and at EOT were 39%/3% vs 40%/9%, 50%/ 8% vs 52%/18%, 70%/5% vs 54%/21%, and 43%/18% vs 58%/32%, respectively (Table 3). Similar results were obtained using baseline dFLC cutoffs of 180 (previously validated to be of prognostic importance in AL) 27 and 50 mg/L (per the definition of measurable disease in AL) 28 (supplemental Table 2). Ongoing on treatment, n 1 1 2 ‡ Alive, n (%) 11 (61) 22 (65) 9 (50) KPS, Karnofsky performance status.…”
Section: Response To Treatmentsupporting
confidence: 75%
See 1 more Smart Citation
“…Overall response rates/CR rates in patients with high vs low baseline dFLC (.124.2 vs #124.2 mg/L, cutoff per the median baseline dFLC) after cycles 1, 2, and 4, and at EOT were 39%/3% vs 40%/9%, 50%/ 8% vs 52%/18%, 70%/5% vs 54%/21%, and 43%/18% vs 58%/32%, respectively (Table 3). Similar results were obtained using baseline dFLC cutoffs of 180 (previously validated to be of prognostic importance in AL) 27 and 50 mg/L (per the definition of measurable disease in AL) 28 (supplemental Table 2). Ongoing on treatment, n 1 1 2 ‡ Alive, n (%) 11 (61) 22 (65) 9 (50) KPS, Karnofsky performance status.…”
Section: Response To Treatmentsupporting
confidence: 75%
“…Higher overall and complete response rates at EOT were observed in patients with low vs high baseline dFLC (using 3 different cutoffs for patient dichotomization: 124. 28 ) and high vs low percentage dFLC decrease at the end of cycle 1 (using cutoffs for patient dichotomization of 59% [median] and 50% [validated cutoff defining dFLC PR] 29 ). The former association may reflect a deeper impact of treatment in patients with lower disease burden at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a novel assay for FLC quantification (N latex FLC, Siemens) based on monoclonals, has been developed and introduced on the market [95]. The performance of the two assays for FLC quantification in AL amyloidosis patients has recently been compared [96,97]. The results showed that the assays have similar diagnostic sensitivity; however, they are not interchangeable and the dynamic range of the N Latex FLC assay is limited.…”
Section: Measurement Of the Amyloidogenic Precursormentioning
confidence: 99%
“…However, CT-guided percutaneous needle biopsy or endoscopic ultrasound biopsy has the greater value in the diagnosis of these diseases [6,7]. So far, the gold standard for the diagnosis of amyloidosis is the histological examination of biopsy tissues through Congo red (pink or rose red) and methyl violet (red or purple) staining, and polarized light microscopy showing the characteristic yellow-green two-color of double refraction bodies [8].…”
Section: Discussionmentioning
confidence: 99%